Global Critical Race Feminism Post 9-11: Afghanistan - Adrien Katherine Wing (Washington University Journal of Law & Policy, 2002)
In essence, Global Critical Race Feminism is concerned with the legal status of women of color around the world. By the term women of color, I refer to groups both inside and outside the United States. In the American context, I am including African Americans, Latinas, Asian, and Native Americans, as well as Arabs, Muslims, and any other group that is being socially constructed as people of color. I have never liked the commonly used term “third world women,” but if one still accepts such a term, then third world women could be considered the fourth world, i.e., the bottom of the bottom. Unfortunately, women in this broad category remain discriminated against in every society in which they live, whether that be in the economic, political, or educational spheres.
Keywords: Critical race feminism; Women -- Afghanistan; Critical race theory (Law); Feminism; World Trade Center and Pentagon Attacks; 2001; Afghanistan; United States